2016
DOI: 10.1016/j.jcat.2016.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Tuning external surface of unit-cell thick pillared MFI and MWW zeolites by atomic layer deposition and its consequences on acid-catalyzed reactions

Abstract: The pillared MWW (PMWW or MCM-36) and pillared MFI (PMFI) zeolites are 2dimensional (2D) catalytically active materials made by pillaring of layered MCM-22(P) and multilamellar MFI precursors, respectively. The single-or near single-unit-cell thick 2D microporous layers in PMWW and PMFI expose comparable number of external surface acid sites (i.e., acid sites enclosed in mesopores between zeolitic layers) to those in micropores, which become important or dominant contributor to the catalytic properties. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 65 publications
3
19
0
Order By: Relevance
“…The most preferable BAS ratio of internal to external pore was calculated to be 2:1, as determined from the DFT energetic preference for different sets of internal and external BAS (the details of the searching procedure are presented in Figure S2 of SI). Such a BAS ratio of internal to external pore on the 2D-PMFI model matches closely with the reported experimental findings, where the experimentally measured fraction of external sites on the PMFI catalyst is determined as ∼32% by dimethyl ether titration and methanol dehydration. , …”
Section: Resultssupporting
confidence: 89%
“…The most preferable BAS ratio of internal to external pore was calculated to be 2:1, as determined from the DFT energetic preference for different sets of internal and external BAS (the details of the searching procedure are presented in Figure S2 of SI). Such a BAS ratio of internal to external pore on the 2D-PMFI model matches closely with the reported experimental findings, where the experimentally measured fraction of external sites on the PMFI catalyst is determined as ∼32% by dimethyl ether titration and methanol dehydration. , …”
Section: Resultssupporting
confidence: 89%
“…The set of experiments showed that the intrinsic catalytic behavior of Brønsted acid sites in PMWW and PMFI was not altered significantly by the ALD treatment. However, a certain selectivity of external acid sites in the alkylation reaction of benzyl alcohol with mesitylene was established [287].…”
Section: Post-synthesis Aluminium Incorporationmentioning
confidence: 99%
“…For example, the FTIR spectra of adsorbed pyridine, collidine, and DTBP molecules have shown that the 2D unilamellar and multilamellar MFI zeolites have a higher fraction of Lewis acidity than that of 3D MFI, while the accessibility of acid sites is improved due to the open structure [247][248][249][250]. The acid site accessibility of pillared MFI and SPP zeolites has been measured by direct DTBP uptake measurements, which maintain the characteristics of the high acid site accessibility in 2D MFI zeolites [173,245,251,252]. In particular, the concentrations of external surface and pore mouth Brønsted acid sites in the pillared MFI zeolite was quantified by a combined dimethyl ether (DME) titration and methanol dehydration in the presence of DTBP or triphenylphosphine (TPP) titrants, respectively [232].…”
Section: Acidity Characterization For 2d Mfi Zeolitesmentioning
confidence: 99%
“…DTBP titration, in combination with DME titration or the ethanol dehydration reaction, was used to evaluate the accessibility of acid sites in the MCM-36 prepared under mild conditions [173,245,251,252]. The ethanol dehydration rates as a function of cumulative DTBP or pyridine titrant addition on the MCM-22 and MCM-36 zeolites, respectively, were measured.…”
Section: Acidity Characterization For 2d Mww Zeolitesmentioning
confidence: 99%